Le genre comme fait de discours : pour une définition molle de la science-fiction - Matthieu Letourneux (ReS Futurae)
In this article we propose to offer a general reflection on media genres based on the case of science fiction. We will try to show that it is as a collective practice, the result of the sedimentation of serial practices and uses, that we can think of a genre. Elaborated collectively in the course of discursive exchanges in the public sphere, resulting in a superimposition of slightly different definitions, the genre must be thought of at the level of the practices of producers and receivers. By unfolding the superimposed definitions of gender, we can thus understand the set of cultural meanings that constitute it. Therefore, it makes little sense to try to impose a universal definition of a genre, since it is nothing more than the result of fragmentary definitions that are sedimented and evolve with new updates. For it is in the gaps between definitions that the individual and collective meaning of science fiction is played out in context.